2016
DOI: 10.1021/acsnano.6b03042
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Flexible, Waterproof, Transparent, and Self-Powered Tactile Sensing Panel

Abstract: Portable and wearable electronic devices are human-centered devices; therefore, many unique attributes are highly desirable, such as flexibility, being self-powered, and waterproof. These properties render devices excellent adaptivity in harsh operation environments. In this work, we report an integrated triboelectric tactile sensor array with flexible, transparent, self-powered, and waterproof features. Each tactile sensor is a surface nano/microtexture enhanced triboelectric nanogenerator. The sensor array c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Transparent conductive electrodes (TCEs) with high conductivity and transparency are essential elements for the advanced optoelectronic devices, such as touchscreen panels (TSPs), solar cells (SCs), and organic light emitting diodes (OLEDs)1234. To date, conductive films including conducting metal oxides, graphene, carbon nanotubes (CNTs), conducting polymers, metal nanowires, metal mesh, ultrathin metal films (UTMFs), and hybrids of them have been reported as potential candidates to replace traditionally indium tin oxide (ITO), which is limited by its fragility, high refractive index, limited indium supplies, and high processing temperature56789101112.…”
mentioning
confidence: 99%
“…Transparent conductive electrodes (TCEs) with high conductivity and transparency are essential elements for the advanced optoelectronic devices, such as touchscreen panels (TSPs), solar cells (SCs), and organic light emitting diodes (OLEDs)1234. To date, conductive films including conducting metal oxides, graphene, carbon nanotubes (CNTs), conducting polymers, metal nanowires, metal mesh, ultrathin metal films (UTMFs), and hybrids of them have been reported as potential candidates to replace traditionally indium tin oxide (ITO), which is limited by its fragility, high refractive index, limited indium supplies, and high processing temperature56789101112.…”
mentioning
confidence: 99%
“…The interlocking structures of AgNWs and PDMS tribo-layers lead to larger effective contact areas than those with flat surfaces, resulting in higher measurement sensitivity. For instance, the micropyramid array patterned triboelectric sensor presented by Jiang et al demonstrated a sensitivity of only 2.82 ± 0.187 mV kPa −1 , [46] while the hemispheres-array-structured TENG pressure sensor reported by Lee et al achieved a sensitivity of ≈28.8 mV kPa −1 . This is potentially due to the fact that the relatively thick film (≈150 µm) of PTFE with large modulus (860 MPa-1.6 GPa [43,44] ), which is about four orders of magnitude larger than PDMS (≈1-3 MPa), [45] results in significantly increased stiffness of the microstructures which prohibits the interlocking contact under external load.…”
Section: Resultsmentioning
confidence: 99%
“…To suppress the cost of frequent exchange of battery modules and to extend the longevity of the products over a few years, efforts are paid to develop a new technology to retrieve electrical power from the environments including vibrations, radio waves, and lights . Even battery‐less sensors are under study to solve the issues associated with the power source.…”
Section: Introductionmentioning
confidence: 99%